Pendampingan Pendidikan Disiplin Karakter Pada Pembiasaan Shalat Dhuha Di Sekolah Dasar - Widi, Widi (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Worship is one way to draw closer to Allah SWT. Worship has two main focuses: mahdhah worship and ghairu mahdhah worship. And one of the mahdhah worship is prayer, which in Arabic is also called "asshalatu" which means prayer. Prayer can also be called ahmad. There are two types of prayer: obligatory prayer and sunnah prayer. Because one of the sunnah prayers commonly performed by Muslims is the sunnah dhuha prayer. The sunnah dhuha prayer has the advantage of fulfilling spiritual needs, beliefs, norms, morals and can also instill discipline in students in worship. In carrying out the dhuha prayer, students will have an orderly, responsible, and orderly attitude both in worship and in their environment. The research method used in this study is a descriptive qualitative method, namely interviews, observation, and documentation. With the subjects of the principal, teachers and students of SDIT Ummi Kota Bengkulu, using source triangulation techniques. The results of the research examined, implementing congregational dhuha prayer at school for students. This way, students become accustomed to performing the Dhuha prayer according to the school's schedule. The school expects children to be disciplined, obedient, and responsible toward their religion and their environment.